2015
DOI: 10.3109/09546634.2015.1109029
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5% amorolfine nail lacquer in Neoscytalidium dimidiatum onychomycosis

Abstract: This study supported that amorolfine nail lacquer provided promising efficacy in the treatment of Neoscytalidium onychomycosis as a novel monotherapy regimen which were superior to topical urea cream with occlusion in every aspect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Chen et al reported a case report of a 16‐month‐old boy who had been successfully treated by 5% amorolfine nail lacquer after the diagnosis of onychomycosis, as systemic treatment with itraconazole and terbinafine in children is not approved by the Food and Drug Administration (FDA) (Chen et al, ). Amorolfine nail lacquer as a novel monotherapy regimen in the treatment of Neoscytalidium onychomycosis which is considered recalcitrant could also provide superior efficacy than topical urea cream with occlusion in every aspect (Bunyaratavej et al, ). Urea ointment under occlusion is applied as atraumatic chemomechanical maceration of the diseased nail, however, the clinical success of it alone is poor, better cure rates can be found with the combination of antifungal agent and nail removal, such as the combination of bifonazole 1% and urea ointment 40%, the efficacy of which is slightly lower than that of amorolfine 5% lacquer (Niewerth & Korting, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported a case report of a 16‐month‐old boy who had been successfully treated by 5% amorolfine nail lacquer after the diagnosis of onychomycosis, as systemic treatment with itraconazole and terbinafine in children is not approved by the Food and Drug Administration (FDA) (Chen et al, ). Amorolfine nail lacquer as a novel monotherapy regimen in the treatment of Neoscytalidium onychomycosis which is considered recalcitrant could also provide superior efficacy than topical urea cream with occlusion in every aspect (Bunyaratavej et al, ). Urea ointment under occlusion is applied as atraumatic chemomechanical maceration of the diseased nail, however, the clinical success of it alone is poor, better cure rates can be found with the combination of antifungal agent and nail removal, such as the combination of bifonazole 1% and urea ointment 40%, the efficacy of which is slightly lower than that of amorolfine 5% lacquer (Niewerth & Korting, ).…”
Section: Discussionmentioning
confidence: 99%
“…onychomycosis at 12 months and 89.3% mycological cure with 5% amorolfine nail lacquer in N. dimidiatum onychomycosis. 25,26 In the latter study, a mycological cure of 32% was noted in those patients marginally higher mycological cure rate of 65% as compared to 60% in those using 5% amorolfine nail lacquer alone. 27 Amphotericin B has excellent in vitro activity against nondermatophyte molds.…”
Section: Discussionmentioning
confidence: 82%
“…Complete cure, as a combination of clinical and mycological cure, being the most desired outcome clinically was reported by two studies [31, 32]. A complete cure was reported in 27.7% [31] and 20% [32] in urea group compared to 20.8% in urea-bifonazole and 50% in amorolfine group, respectively.…”
Section: Resultsmentioning
confidence: 98%